2012
DOI: 10.1016/j.pog.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de un programa de ejercicio físico supervisado sobre la estructura cardiaca durante la gestación. Ensayo clínico aleatorizado

Abstract: Recibido el 11 de julio de 2011; aceptado el 11 de enero de 2012 Accesible en línea el 22 de marzo de 2012 PALABRAS CLAVE Embarazo; Ejercicio físico; Sistema cardiovascularResumen Objetivo: Analizar la seguridad del ejercicio aeróbico para el sistema cardiovascular de las mujeres gestantes y valorar las posibles mejoras cardiovasculares producidas.Sujetos y métodos: Se diseñó un ensayo clínico aleatorizado, no apareado, no enmascarado. El registro de datos se realizó en las semanas 20 y 34 de gestación. En la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
3
0
6
Order By: Relevance
“…Cardiovascular changes have been described in pregnant women under a supervised exercise program during pregnancy [17,18]. Perales et al [19] described that, pregnant women under a supervised mild exercise program, have significant lower heart rate levels, lower blood systolic and diastolic pressure. Moreaver, a randomized controlled study [5] found that aerobic exercise reduced resting systolic blood pressure in normotensive pregnant women and reflected a positive adaptation of the maternal cardiovascular system.…”
Section: Cardiovascular Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular changes have been described in pregnant women under a supervised exercise program during pregnancy [17,18]. Perales et al [19] described that, pregnant women under a supervised mild exercise program, have significant lower heart rate levels, lower blood systolic and diastolic pressure. Moreaver, a randomized controlled study [5] found that aerobic exercise reduced resting systolic blood pressure in normotensive pregnant women and reflected a positive adaptation of the maternal cardiovascular system.…”
Section: Cardiovascular Outcomesmentioning
confidence: 99%
“…Cardiovascular changes at rest have been described in pregnant women that are under a supervised mild-moderate exercise program during pregnancy, like lower heart rate levels or lower heart blood systolic and diastolic pressures [2][3][4][5]. This would reflect a positive adaptation of the maternal cardiovascular system to the exercise and it may reduce the risk of preeclampsia during pregnancy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tras una revisión bibliográfica, encontramos que los últimos estudios se ha demostrado que el ejercicio en la mujer embarazada no solo previene la ganancia excesiva de peso en esta etapa (15)(16)(17)(18) que se asocia a diabetes gestacional (19)(20)(21) sino también la hipertensión arterial (22)(23)(24)(25). El beneficio no sólo es para la madre sino también para el feto, pues disminuye el riesgo de macrosomía y todo esto facilita un parto más fisiológico (26)(27)(28)(29).…”
Section: Introductionunclassified
“…Based on a previous pilot study conducted by our research group 148 , we anticipated a difference of 5 ml/beat in stroke volume between CG and EG in late pregnancy (34 th weeks). Two-sided 5% significance level and a power of 80% were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Basándonos en un estudio piloto previo realizado por el presente grupo de investigación 148 , se anticipó una diferencia de 5 ml/latido en el VS entre GC y el GE en el 3ºT de embarazo (semana 34). Considerando una significación bilateral del 5% y un poder estadístico del 80%, el tamaño muestral necesario fue de 65 mujeres embarazadas por grupo de estudio.…”
Section: Análisis Estadísticounclassified